AN UPDATED STAGING SYSTEM OF TYPE 3 NEOVASCULARIZATION USING SPECTRAL DOMAIN OPTICAL COHERENCE TOMOGRAPHY. (December 2016) - Su, Daniel; Lin, Shawn; Phasukkijwatana, Nopasak; Chen, Xuejing; Tan, Anna; Freund, K. Bailey; Sarraf, David
Abstract : Purpose: To comprehensively investigate spectral domain optical coherence tomography features associated with Type 3 neovascularization and determine the prevalence of each feature and to develop an updated staging system for Type 3 neovascularization based on spectral domain optical coherence tomography findings. Methods: The authors retrospectively analyzed 34 eyes with new-onset Type 3 neovascularization. Spectral domain optical coherence tomography images at onset of Type 3 neovascularization, immediately after the first injection, and at the final quiescent visit were analyzed for the presence of specific optical coherence tomography features. In addition, when available, optical coherence tomography images from the visit before onset were studied. Results: Among 18 eyes with preonset optical coherence tomography, 77.8% had preexisting intraretinal hyperreflective foci (precursor lesion). In the same group of eyes, 44.4% and 27.8% exhibited outer plexiform layer disruption and outer plexiform layer downward deflection, respectively. At the onset of detectable Type 3 neovascularization, all 34 eyes demonstrated a hyperreflective focus with cystoid macular edema and 85.3% exhibited disruption of the retinal pigment epithelium. Serous pigment epithelial detachment and subretinal fluid were present in 67.6% and 23.5% of eyes at onset, respectively. The rate of cystoid macular edema decreased from 100% to 17.6% after a single injection. At the final quiescent visit, focal atrophy at the site of Type 3 lesions, as evidenced by outer retinal and retinal pigment epithelium disruption developed in 88.2% and 52.9% of eyes, respectively. Conclusion: An updated staging system of Type 3 lesions was developed based on spectral domain optical coherence tomography findings. A precursor stage consists of a punctate hyperreflective focus in the outer retina. The subtle detection of associated outer plexiform layer disruption and downward deflection may indicate that this precursor lesion is more likely to progress to an active Type 3 neovascular lesion. Stage 1 consists of a larger intraretinal hyperreflective lesion associated with cystoid macular edema but without outer retinal disruption. Stage 2 is notable for outer retinal disruption that occurs with retinal pigment epithelium disruption in most of the cases. Stage 3 is defined by an intraretinal hyperreflective lesion that extends through the retinal pigment epithelium to vascularize a drusenoid pigment epithelial detachment creating a serous component of the pigment epithelial detachment. Abstract : The authors retrospectively analyzed 34 eyes with Type 3 neovascularization using spectral domain optical coherence tomography. The presence of specific optical coherence tomography features and their prevalence were analyzed and used to develop an updated staging system for Type 3 lesions based on optical coherence tomography findings.